2019
DOI: 10.1088/1757-899x/505/1/012114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epoxidised natural rubbers on curing characteristics of kaolin-filled natural rubber composites

Abstract: Effects of 2 types of epoxidised natural rubbers (ENR 25, ENR 50), with twenty-five and fifty moles of epoxidation, on crosslinking density and cure characteristics of natural rubber (NR) composites, which were filled by kaolin filler, were investigated using a semi efficient vulcanisation system. The ENRs were added separately into composites at 5.0, 10.0, 15.0, 20.0 and 25.0 parts per hundred rubber. An observation was conducted to investigate the effects of the ENRs on curing and crosslinking density of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The optimum cure time, š‘”š‘” š‘š‘90 for NR compounds decreases significantly with greater fibre content. Reduce in š‘”š‘” š‘š‘90 corresponds to a higher cure rate of the NR compounds [25]. In other words, the presence of fibre serves as curative components that improve the cure rate.…”
Section: Cure Characteristicsmentioning
confidence: 99%
“…The optimum cure time, š‘”š‘” š‘š‘90 for NR compounds decreases significantly with greater fibre content. Reduce in š‘”š‘” š‘š‘90 corresponds to a higher cure rate of the NR compounds [25]. In other words, the presence of fibre serves as curative components that improve the cure rate.…”
Section: Cure Characteristicsmentioning
confidence: 99%
“…Chalk exhibits the same deficiency of polar surface chemistry. It is difficult to moisten and disperse in the natural rubber, so the interaction with the rubber matrix is weak [58,59]. Thus, for a better interaction between precipitated silica or chalk and natural rubber matrix, the maleated natural rubber (NR-g-AM) was used.…”
Section: Filler Type In Compositesmentioning
confidence: 99%
“…The mechanical properties were found to be degraded due to poor dispersion of the CaCO 3 in the NR matrix. Surya et al [ 16 ] revealed a possibility to enhance the rubberā€“filler interactions of CaCO 3 filler in NR by adding epoxidized natural rubber as a compatibilizer. Despite the various studies conducted, the effects of CaCO 3 on the final properties of NR composites remain entirely unexplored.…”
Section: Introductionmentioning
confidence: 99%